2014
DOI: 10.1111/apha.12314
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of calcium homoeostasis in cultured rat astrocytes evoked by bioactive sphingolipids

Abstract: Exogenously added cell-permeable sphingosine-like lipids exert complex, Ca(2+)-dependent effects on astrocytes and likely alter their homeostatic function in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 68 publications
(70 reference statements)
2
27
0
Order By: Relevance
“…The structural analogy of FTY720 with sphingosine could underlie the observed recruitment of synaptobrevin for SNARE complex assembly thereby enhancing regulated exocytosis. Although our data do not rule out further effects of FTY720 which could contribute to enhanced exocytosis 9 , we would like to propose that this sphingomimetic drug can also uplift the cytoplasmic part of synaptobrevin thereby activating SNARE assembly for vesicle exocytosis. We do not necessarily envisage that FTY720 directly binds to synaptobrevin – it is possible that after incorporation into the synaptic vesicle membrane the positively charged amphiphilic FTY720 changes the interface between synaptobrevin and the negatively charged surface of the vesicular membrane.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…The structural analogy of FTY720 with sphingosine could underlie the observed recruitment of synaptobrevin for SNARE complex assembly thereby enhancing regulated exocytosis. Although our data do not rule out further effects of FTY720 which could contribute to enhanced exocytosis 9 , we would like to propose that this sphingomimetic drug can also uplift the cytoplasmic part of synaptobrevin thereby activating SNARE assembly for vesicle exocytosis. We do not necessarily envisage that FTY720 directly binds to synaptobrevin – it is possible that after incorporation into the synaptic vesicle membrane the positively charged amphiphilic FTY720 changes the interface between synaptobrevin and the negatively charged surface of the vesicular membrane.…”
Section: Discussionmentioning
confidence: 57%
“…The need for well-defined therapeutic targets for FTY720 and related drugs has been highlighted 8 . Recent studies demonstrated the role of FTY720 on specific functions of astrocytes such as cytoskeleton 10, 45 , vesicle traffic and calcium homeostasis 9, 46 . In PC12 neuronal model cells, micromolar concentrations of FTY720 activated intracellular protein phosphatase 2 A (PP2A), an important modulator of neuronal function 47 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that ATP stimulation transiently attenuates endo/lysosomal vesicle mobility in astrocytes . Thus we investigated whether nestin deficiency interferes with the stimulation‐dependent attenuation of vesicle mobility.…”
Section: Resultsmentioning
confidence: 99%
“…In astrocytes, sphingosine analogue FTY720 (fingolimod), currently used for treatment of multiple sclerosis, strongly affects vesicle mobility and the release of peptides from a single vesicle [84]. This is associated with a change in Ca 2+ homeostasis in astrocytes [85]. …”
Section: Vesicle Traffic Surface Signalling Landscape Of Astrocytmentioning
confidence: 99%